Institutionalizing interprofessional education in small states: perspectives from faculty and key stakeholders in Malta. Issue 1 (2nd January 2020) - Bonello, Marjorie; Morris, Jane
ABSTRACT: The benefits of a collaborative practice-ready workforce for patient-centered care are internationally gaining momentum and the Interprofessional education (IPE) movement is contributing to this. In the small island state of Malta, the importance of a collaborative health-care workforce is being promoted and endorsed in policy documents. However, IPE has not yet been formally integrated into professional health education curricula. This qualitative case study aimed to explore stakeholders' perspectives and perceptions of a possible IPE initiative at the Faculty of Health Sciences, University of Malta. A purposive sampling method with 59 participants including academics and senior policy-makers was used. Data were gathered through focus groups, one-to-one interviews and documentary searches and analyzed using a 'Framework' approach supported by NVivo 10. Four major themes were identified encompassing enablers and barriers for IPE: a) IPE could be beneficial, b) institutional and organizational barriers, c) professional barriers, and d) cultural barriers. This study highlights a range of interdependent challenges in the implementation of IPE from the perspective of the small state of Malta that can nonetheless contribute insights for other smaller sized nations for the development and formalization of collaborative innovations in the educational curricula of health professionals. In particular, it highlights that national cultural dimensions or traits may represent a relatively unexplored barrier to date for the successful implementation of IPE in specific countries.